2015
DOI: 10.1590/1809-4430-eng.agric.v35n6p1198-1209/2015
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento multitemporal da cobertura de terra, por meio de árvore de decisão, na bacia hidrográfica do rio Marombas-SC

Abstract: RESUMO O conhecimento sobre a cobertura da terra é fundamental como informação para o planejamento e o estudo dos efeitos da substituição de paisagens naturais por paisagens antropizadas. Este estudo objetivou analisar a dinâmica da cobertura da terra entre os anos de 1989 e 2011, na bacia hidrográfica do rio Marombas (SC), empregando o classificador árvore de decisão (AD). Foram utilizadas bandas espectrais do satélite Landsat 5, índices de vegetação e atributos de terreno extraídos do modelo digital de eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Landsat satellite images are used to identify and evaluate changes in vegetation coverage structure, physiognomy and dynamics, making it possible to study changes in soil coverage at a spatial and temporal scale, at low cost and with better accuracy (Oliveira, 2015;Silva et al, 2016;Silva et al, 2019). Several authors have found that precipitation before the satellite passes affects the spectral response of orbital images (Ponzoni and Shimabukuro, 2010;Caten et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landsat satellite images are used to identify and evaluate changes in vegetation coverage structure, physiognomy and dynamics, making it possible to study changes in soil coverage at a spatial and temporal scale, at low cost and with better accuracy (Oliveira, 2015;Silva et al, 2016;Silva et al, 2019). Several authors have found that precipitation before the satellite passes affects the spectral response of orbital images (Ponzoni and Shimabukuro, 2010;Caten et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2009) used the NDVI, MSDI and surface albedo to evaluate and determine the degree of degradation on the Ordos Plateau in China with images of Landsat-4, 5 and 7 on a regional scale. Caten et al (2015) used the AD classifier to analyze soil coverage dynamics between 1989 and 2011, in the Marombas river basin, Santa Catarina. Vorovencii (2015) based on albedo, MSDI and Vegetation Index Soil-Adjusted (SAVI) obtained from the Landsat-5 satellite applied the AD classifier to assess the risk of desertification in Romania, in the years 1987 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os métodos disponíveis para identificação das coberturas da terra, a distinção de classe pela fotointerpretação, por ser um processo manual, é oneroso, e a qualidade e confiabilidade dos resultados variam, principalmente, de acordo com a habilidade e experiência do fotointérprete (ALMEIDA FILHO et al, 1998). A distinção pelo processo de classificação de imagens, por ser automatizado, torna o processo mais rápido, e a qualidade e a confiabilidade variam, principalmente, de acordo com o algoritmo de classificação adotado (CATEN et al, 2015), tipo de classificador (supervisionado ou não supervisionado), método de classificação (pixel-a-pixel ou por região), assim como, experiência e habilidade da equipe (MELLO et al, 2012).…”
Section: Introductionunclassified